Higher education administration with social media - Wankel, Laura A.; Wankel, Charles (Cutting-edge technologies in higher education, 2011)
New technologies provide new ways of delivering the programs and services of higher educational (HE) institutions. Social media such as Facebook, blogs, Flickr, Twitter, and the Second Life virtual world engage constituents and enhance effectiveness. Understanding the trends in the expanding role of social media in HE and the related implications for staff preparedness and training is necessary for future-oriented administrators and practitioners. This book examines how social media are redefining what university communities are and the purposes and practices of the various functional areas in HE. It presents an overview of innovative practices in the recruitment, advising, retention, graduation and engagement of students and alumni, and examines social media in connection with enrollment management, advising and mentoring, public relations and alumni relations. Topics covered include: how Facebook helps and hinders students social integration; connecting fans and sports more intensively through social media; how to prepare staff to use social media in robust ways; and using social networking sites during the career management process, for social research and studying abroad.